2017
DOI: 10.1186/s12889-017-4208-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, perception and factors associated with diabetes mellitus among the adult population in central Vietnam: a population-based, cross-sectional seroepidemiological survey

Abstract: BackgroundDiabetes Mellitus (DM) has rapidly become a major public health concern in Vietnam. Although the prevalence of DM has been studied in northern and southern Vietnam, little data are available for the central region. Therefore, the aims of this survey were to estimate the prevalence of DM and to identify the perception of and factors associated with DM among the adult population in central Vietnam.MethodsWe conducted a cross-sectional, population-based survey in Khánh Hòa Province, Vietnam in December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 12 publications
(15 reference statements)
3
20
0
1
Order By: Relevance
“…The finding is also comparable with study report of sub national studies in Asia including Indian industrial community, 38.4% [44] and central Vietnam, 44.6% [47]. Thus, efforts have to be made, particularly by the individuals involved in health practice, to early detect the disease and thereby initiate a suitable therapeutic service, before complications, arise.…”
Section: Behavioral Diet and Physical Measurement Of The Study Partsupporting
confidence: 84%
“…The finding is also comparable with study report of sub national studies in Asia including Indian industrial community, 38.4% [44] and central Vietnam, 44.6% [47]. Thus, efforts have to be made, particularly by the individuals involved in health practice, to early detect the disease and thereby initiate a suitable therapeutic service, before complications, arise.…”
Section: Behavioral Diet and Physical Measurement Of The Study Partsupporting
confidence: 84%
“…There are several studies about the risk factors for OW/OB in Vietnam. A study performed in central Vietnam showed that BMI was the largest contributor to diabetes mellitus risk, with an OR of more than ten times compared to low-and normal-BMIs [18]. Therefore, preventing OW/OB in children plays an important role in preventing NCDs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the diabetes prevention program at the Centers for Disease Control and Prevention (CDC) has facilitated primary health care, which includes suggestions on how to empower patients, help them to take control of their blood sugar and follow a self-controlled diet [35]. However, the findings suggest that 67% of the participants had never heard of DM [23], and only 3.9% had a moderate or above knowledge level about the dangers and complications of the disease; additionally, only 0.6% had experience with the risk factors, and 21.9% had knowledge about the prevention and treatment of diabetes [18]. Abdominal obesity (obesity by the waist-hip ratio [WHR]) was positively associated with female gender (OR 43.64, 95% CI 13.15-144.86); however, it was negatively associated with smokers and people aged ≥60 in ethnic groups other than the Kinh and Tay religions [21].…”
Section: Smoking and Lack Of Knowledge About Diabetesmentioning
confidence: 99%
“…However, there have been no studies conducted in the provinces with ethnic minorities to analyze the incidence of diabetes among these ethnic groups [22]. A cross-sectional study identifying the perception of and factors associated with DM showed that participants aged 60-70 years were more likely to have DM than those aged 30-39 years, and participants classified as obese were more likely to have DM than those with a healthy or low BMI [23]. The results of a multivariate logistic regression model unveiled the proportion of the Kinh ethnic group with diabetes as being 19.7 higher than that of an ethnic minority group, and this difference was statistically significant (OR = 19.7; 95% CI:…”
Section: Introductionmentioning
confidence: 99%